Analisis Pengendalian Kualitas Produk Cacat Menggunakan Metode Lean Six Sigma dengan Konsep DMAIC di PT. PQR - Wicaksono, Rizky Adib; Momon S, Ade; Wahyudin, Wahyudin; Malik Ij, Falih Abdul; Setyanto, M. Ulfi Akhsan (Fakultas Teknik Universitas Tulang Bawang, 2026)
A high defect rate is a critical issue in the manufacturing industry as it affects efficiency and product quality. PT. PQR still experiences defects in the production of Part Member Sub Assy FR Under RH. This study aims to analyze defect levels, identify dominant defects, and propose improvements using the Lean Six Sigma approach with the DMAIC method. A descriptive quantitative method was employed using secondary production and defect data from June to October 2023. The results show that the dominant defects are Part Gap (79%) and Welding CO Blow Hole (21%). The highest DPMO value is 27,617.6, with the lowest sigma level of 3.417 occurring in July, indicating that the process capability is not yet optimal. The defects are mainly caused by human, material, machine, and environmental factors. It is concluded that Lean Six Sigma with the DMAIC method is effective as a systematic framework to improve quality and reduce defect rates. Keywords: DMAIC, Manufacturing Industry, Lean Six Sigma, Quality Control, Defective Product.